2016
DOI: 10.1093/fpa/orw019
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Radical Parties in Coalition Foreign Policy: Italy, Hijacking, and the Extremity Hypothesis

Abstract: Scholars increasingly suggest that coalition governments produce more extreme foreign policies than single-party governments. Extremity is especially likely when governments include radical parties that take extreme positions on foreign policy issues and are "critical" to the government's survival, as the radical parties push the centrist ones toward the extremes. A look at Italy's Second Republic provides an important counterpoint to the extremity hypothesis. In three high-profile cases of military operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
(13 reference statements)
0
11
0
2
Order By: Relevance
“…Nevertheless, the attention paid to Italian parties and defence policy has generally remained inadequate. There are few studies on the nexus between parliament and defence issues (Bono 2005; D’Amore 2001), on parties and coalition foreign policy (Coticchia and Davidson 2018; Verbeek and Zaslove 2015) and almost none on voting patterns across the entire post-Cold War period 1 . Indeed, the above-mentioned consequences of parliamentary oversight on defence policy have never been examined in the case of Italy.…”
Section: The Case Of Italymentioning
confidence: 99%
“…Nevertheless, the attention paid to Italian parties and defence policy has generally remained inadequate. There are few studies on the nexus between parliament and defence issues (Bono 2005; D’Amore 2001), on parties and coalition foreign policy (Coticchia and Davidson 2018; Verbeek and Zaslove 2015) and almost none on voting patterns across the entire post-Cold War period 1 . Indeed, the above-mentioned consequences of parliamentary oversight on defence policy have never been examined in the case of Italy.…”
Section: The Case Of Italymentioning
confidence: 99%
“…In line with Coticchia and Davidson (2018), I hypothesize two causal mechanisms leading to this outcome: lack of salience attributed by the junior partner to security policy and fear of being punished by voters for the collapse of the government. On the basis of extensive qualitative empirical material, including interviews to policymakers, newspaper articles, memoirs and reports of the parliamentary debates, I highlight how these two mechanisms played out differently in the two cases.…”
Section: Introductionmentioning
confidence: 79%
“…In line with Coticchia and Davidson (2018), I hypothesize two elements underlying junior partner's decision to stay in government despite a disliked foreign policy outcome, and in particular, the decision to participate in a military intervention: low salience attributed to the issue and fear of being blamed by voters for the collapse of the cabinet. These two explanations are neither exclusive nor exhaustive: they may verify in conjunction and be complemented by other factors.…”
Section: Hypothesesmentioning
confidence: 92%
See 1 more Smart Citation
“…However, while their analysis of parliamentary voting data confirms that radicalleft parties tend to oppose military deployments, their data only include four MPs of radical-right parties, who never voted against military deployment. The case studies of Verbeek and Zaslove (2015) and Coticchia and Davidson (2016) on the impact of radical parties in Italian government coalitions suggested that extreme parties were less supportive of the use of force, but that this did not prevent the government from deploying military force. Given that empirical research has not yet arrived at conclusive results on the foreign policy preferences of radical parties, the fifth hypothesis is based on the more traditional left-right axis:…”
Section: Involvement Fractionalization and Ideological Orientation mentioning
confidence: 99%